Muscle Pain: Understanding the Mechanisms - Mense, Siegfried; Gerwin, Robert D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
As one half of a comprehensive two-volume publication that covers every angle of muscle pain and is edited by two of the leading figures in the field, this volume details the basic mechanisms of chronic muscle pain syndromes. It provides the practitioner with a deeper understanding of the physical processes involved in these often misunderstood conditions, and in clarifying the nature of muscle pain enables health care professionals to provide more effective treatment.
Preface.-Foreword -- Introduction -- Neuroanatomy of muscle: the muscle nociceptor.Peripheral mechanisms of muscle pain: response behaviour of muscle nociceptors and factors eliciting local muscle pain. Central nervous pathways of muscle pain and descending pain-modulating systems. Referral of muscle pain and transition from acute to chronic pain. Increased muscle tone as a cause of muscle pain. Influence of muscle pain on motor performance -- Glossary.
Keywords: Medicine; Human physiology; Neurosciences; Toxicology; Anesthesiology; Neurology; Rheumatology; Biomedicine; Neurosciences; Human Physiology; Neurology; Pharmacology/Toxicology.; Anesthesiology; Rheumatology